2014
DOI: 10.1159/000362451
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Diseases Enhance Expression of Tetraspanin-8: A Possible Protective Effect against Tubular Injury

Abstract: Background/Aims:TSPAN8 encoding tetraspanin-8 was identified as a candidate gene for immunoglobulin A nephropathy (IgAN) by a genome-wide association study using microsatellites in the Japanese population. Tetraspanin-8 is a cell surface protein that contributes to the migration and invasion of epithelial cells. Methods: We performed immunohistochemistry for tetraspanin-8 on human renal biopsy specimens associated with IgAN, antineutrophil cytoplasmic antibody-associated nephropathy and interstitial nephritis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We performed immunohistochemistry for tetraspanin-8 on human renal biopsy specimens associated with IgAN. 31 In this study, we found that tetraspanin-8 was often expressed in vascular smooth muscle cells and occasionally in tubule cells in normal kidneys, and the degree of tubular staining negatively correlated with the estimated glomerular filtration rate, independently of the type of nephropathy. 31 Further studies are needed to clarify the molecular mechanism underlying the tetraspanin-mediated development of IgAN.…”
Section: Tspan8-ptprrmentioning
confidence: 49%
See 1 more Smart Citation
“…We performed immunohistochemistry for tetraspanin-8 on human renal biopsy specimens associated with IgAN. 31 In this study, we found that tetraspanin-8 was often expressed in vascular smooth muscle cells and occasionally in tubule cells in normal kidneys, and the degree of tubular staining negatively correlated with the estimated glomerular filtration rate, independently of the type of nephropathy. 31 Further studies are needed to clarify the molecular mechanism underlying the tetraspanin-mediated development of IgAN.…”
Section: Tspan8-ptprrmentioning
confidence: 49%
“…31 In this study, we found that tetraspanin-8 was often expressed in vascular smooth muscle cells and occasionally in tubule cells in normal kidneys, and the degree of tubular staining negatively correlated with the estimated glomerular filtration rate, independently of the type of nephropathy. 31 Further studies are needed to clarify the molecular mechanism underlying the tetraspanin-mediated development of IgAN. Furthermore, studies are required to elucidate their function in the pathogenesis or progression of the disease due to interactions between Tspan8 and CD151 as a risk for IgAN.…”
Section: Tspan8-ptprrmentioning
confidence: 49%
“…Still another role for TSPAN8 is seen during kidney disease in Humans; where TSPAN8 is believed serve a protective role (Pan et al). TSPAN8 may also provide protection during cold stress by forming membrane microdomains with other proteins to maintain membrane cryostability and fluidity, which is essential for resisting low temperature stress (Champy et al;Hirukawa et al;Cossins and Prosser, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Tspan8 is also expressed in the stomach and duodenum, and it is required for acinar, gastric, and duodenal development ( Jarikji et al, 2009 ). Enhanced Tspan8 expression identified in injured distal tubules of the kidney may contribute to tubule repair by facilitating migration and invasion of tubule cells ( Hirukawa et al, 2014 ). Moreover, Tspan8 is expressed in the hippocampus and cerebellum of the brain, and participates in the development and maintenance of neuronal circuits through regulation of the expression of downstream genes, such as neurotrophic receptor tyrosine kinase 2 ( Schartner et al, 2017 ).…”
Section: Tspans In Metastasis Of Digestive System Tumorsmentioning
confidence: 99%